Regulation of brain anandamide by acute administration of ethanol - Belén Ferrer; Francisco J. Bermúdez‐Silva; Ainhoa Bilbao; Lily Alvarez‐Jaimes; Irene Sánchez-Vera; Andrea Giuffrida; Antonia Serrano; Elena Baixerás; Satishe Khaturia; Miguel Navarro; Loren H. Parsons; Daniele Piomelli; et al. (2007)
The endogenous cannabinoid acylethanolamide AEA (arachidonoylethanolamide; also known as anandamide) participates in the neuroadaptations associated with chronic ethanol exposure. However, no studies have described the acute actions of ethanol on AEA production and degradation. In the present study, we investigated the time course of the effects of the intraperitoneal administration of ethanol (4 g/kg of body mass) on the endogenous levels of AEA in central and peripheral tissues. Acute ethanol administration decreased AEA in the cerebellum, the hippocampus and the nucleus accumbens of the ventral striatum, as well as in plasma and adipose tissue. Parallel decreases of a second acylethanolamide, PEA (palmitoylethanolamide), were observed in the brain. Effects were observed 45–90 min after ethanol administration. In vivo studies revealed that AEA decreases were associated with a remarkable inhibition of the release of both anandamide and glutamate in the nucleus accumbens. There were no changes in the expression and enzymatic activity of the main enzyme that degrades AEA, the fatty acid amidohydrolase. Acute ethanol administration did not change either the activity of N-acyltransferase, the enzyme that catalyses the synthesis of the AEA precursor, or the expression of NAPE-PLD (N-acylphosphatidylethanolamine-hydrolysing phospholipase D), the enzyme that releases AEA from membrane phospholipid precursors. These results suggest that receptor-mediated release of acylethanolamide is inhibited by the acute administration of ethanol, and that this effect is not derived from increased fatty acid ethanolamide degradation.